2021
DOI: 10.3389/fenrg.2021.640960
|View full text |Cite
|
Sign up to set email alerts
|

Photonic Curing of Nickel Oxide Transport Layer and Perovskite Active Layer for Flexible Perovskite Solar Cells: A Path Towards High-Throughput Manufacturing

Abstract: High-throughput roll-to-roll (R2R) manufacturing of perovskite solar cells (PSCs) is currently limited by thermal processes that take tens of minutes each, translating to impractically long annealing tools at high web speeds. In addition, PSCs are usually made with metal oxide transport layer materials that require high temperatures for thermal annealing. Here, we demonstrate the fabrication of PSCs using photonic curing, instead of thermal annealing, to convert NiOx directly from sol-gel precursors for hole t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Perovskite precursor films absorb the radiant energy from the light pulses and convert them to the perovskite phase. It has been shown that this technique can complete the conversion to perovskite in a few milliseconds and is the fastest post-deposition process. Furthermore, PC is versatile and can convert both the transport layer and the perovskite layer under different processing conditions. , Previously, we have reported using PC to achieve a champion power conversion efficiency (PCE) of 11.26% in a conversion time of 20 ms, which is lower than that of the thermally annealed devices. We note that all the processes with a conversion time of ≤ 2.5 s produce inferior device PCE compared to their thermally annealed counterparts. ,,, Thus, it is critical to understand the reasons behind the inferior PCE of PSCs made by ultrafast processes and explore mitigation strategies to make PSCs with high throughput without compromising performance.…”
Section: Introductionmentioning
confidence: 99%
“…Perovskite precursor films absorb the radiant energy from the light pulses and convert them to the perovskite phase. It has been shown that this technique can complete the conversion to perovskite in a few milliseconds and is the fastest post-deposition process. Furthermore, PC is versatile and can convert both the transport layer and the perovskite layer under different processing conditions. , Previously, we have reported using PC to achieve a champion power conversion efficiency (PCE) of 11.26% in a conversion time of 20 ms, which is lower than that of the thermally annealed devices. We note that all the processes with a conversion time of ≤ 2.5 s produce inferior device PCE compared to their thermally annealed counterparts. ,,, Thus, it is critical to understand the reasons behind the inferior PCE of PSCs made by ultrafast processes and explore mitigation strategies to make PSCs with high throughput without compromising performance.…”
Section: Introductionmentioning
confidence: 99%
“…The intense pulsed light is a non-contact rapid heating method which can offer fast millisecond pulses of broad spectrum light (190-1100 nm) from xenon lamps [74]. Xenon lamps are used to provide high-energy pulse light to 150 J/cm 2 for perovskite annealing, and can achieve thin film crystallization at the millisecond scale [54,70,[75][76][77][78][79]. Druffel et al successfully employed intense pulsed light generated by a xenon lamp to sintering of MAPbI 3 on a mesoporous TiO 2 substrate for first time [76].…”
Section: Electromagnetic Wave Annealingmentioning
confidence: 99%
“…The diiodomethane (CH 2 I 2 ) additive can also improve surface coverage during rapid crystallization and enhance carrier transport [70]. The intense pulse annealing with halogen lamps was compatible with roll-to-roll manufacturing, which enabled production speeds of 26 m/min [77].…”
Section: Electromagnetic Wave Annealingmentioning
confidence: 99%
“…ALD processes are self-limiting in principle, can be fine-tuned to result in ultrathin films of any required thickness, and are compatible with high throughput roll-to-roll (R2R) manufacturing. ALD of lead halide perovskites will allow for greater control over the growth, morphology, and uniformity of the deposited thin films. Lead halide perovskites are most often deposited by spin coating, a type of solution processing that is restricted to small-area substrates and lacks reliability and conformality.…”
Section: Introductionmentioning
confidence: 99%